Real-time Kinematic Positioning Test and Analysis Based on Railway Scene - ZHANG Hu; XIAO Lizhi (Kongzhi Yu Xinxi Jishu)
In recent years, with the wide application of global navigation satellite system (GNSS) positioning technology, train positioning technology in railway industry has gradually developed from traditional rough positioning to high-precision real-time dynamic (RTK) positioning. Traditional GNSS products have some defects in RTK positioning, such as low proportion of fixed solution, unstable fixed solution and lack of long baseline distance supporting, which could lead to low success rate of locomotive control. This paper puts forward a viewpoint of customized optimization design for GNSS products according to the locomotive environment, improving the proportion and stability of RTK fixed solution, increasing the baseline distance to 100 km, and formulates a set of test and analysis scheme. Practical tests verified the optimization effect. Since 2019, the GNSS products tested and screened by the scheme in this paper have been successfully applied to LKJ-15C system, and have completed stable and reliable operation on dozens of electric locomotives, realizing high precision positioning applications such as intelligent driving, automatic benchmarking and automatic shunting protection.